Geospatial Scenario Analysis of Storm Surge in Tandag City - TAWAS, SHEILA KYLENE A.; MILLAN, MA. SHELLA R.; ENDERES, REVELYN G.; LUMCANG, CLARENCE R.; SURILLA, JESTONE T. (The journal of contemporary issues in business and government, 2021)
This paper on storm surge scenario analysis was conducted to determine the geographical extent of storm surge in Tandag City, Surigao del Sur. The study aimed to address the following: (a) to assess the geographic extent of a simulated storm surge (b) to quantify the population distribution reached by the storm surge (c) serve as aid for analysts, policy and decision makers in storm surge disaster risk mitigation. The study overlaid the data in QGIS, and calculated the affected and populated areas exposed to storm surge. The results revealed that majority of the coastal barangays are exposed to storm surge. The storm surge has a tidal level of 3-4 meters which can damage properties and put lives in danger in the affected area. Out of the 21 barangays, four (4) barangays are highly vulnerable to storm surge, with a 55% exposure, and 1 barangay is 100% exposed to 4-meter storm surge. Among these barangays, Brgy. Dagocdoc has a land area and population exposed to 100% storm surge 4-meters high, while Brgy. Bag-ong Lungsod can have the highest percentage of affected population at (86.95%). This study can shed light to LGU to incorporate scientific study to their land use plan and disaster risk management plan.